+0  
 
0
332
2
avatar
Guest Apr 2, 2015

Best Answer 

 #1
avatar+17745 
+5

f(x + 1)  =  x2 - 3x + 2   --->   f(x + 1)  =  (x - 2)(x - 1)   --->   f(x)  =  (x - 3)(x - 2)

f(x)  =  0   --->   (x - 3)(x - 2)  =  0   --->   x  =  2  or  x  =  3

Sum  =  2 + 3  =  5 

geno3141  Apr 2, 2015
 #1
avatar+17745 
+5
Best Answer

f(x + 1)  =  x2 - 3x + 2   --->   f(x + 1)  =  (x - 2)(x - 1)   --->   f(x)  =  (x - 3)(x - 2)

f(x)  =  0   --->   (x - 3)(x - 2)  =  0   --->   x  =  2  or  x  =  3

Sum  =  2 + 3  =  5 

geno3141  Apr 2, 2015
 #2
avatar+93351 
0

That is another really tricky little question.

thanks Geno :)

Melody  Apr 3, 2015

37 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.